Changes in Gastric Mucosal Glycosylation Before and After Helicobacter pylori Eradication Using Lectin Microarray Analysis - Ogawa, Ryo; Okimoto, Tadayoshi; Kodama, Masaaki; Togo, Kazumi; Fukuda, Kensuke; Okamoto, Kazuhisa; Mizukami, Kazuhiro; Murakami, Kazunari (Turkish Journal of Gastroenterology, 2022)
Background: Glycosylation is a common post-translational modification, and it has been reported that alterations in the glycosylationpatterns on cells are related to cell proliferation, differentiation, tissue adhesion, and carcinogenesis. This study aimed to investigate therelationship between Helicobacter pylori infection and gastric mucosal glycosylation using a lectin microarray system.Methods: Gastric mucosal samples were obtained from 10 Helicobacter pylori-non-infected patients, 10 H. pylori-infected patients, and10 after H. pylori-eradicated patients who underwent gastric mucosal biopsy by endoscopy in our institute. The gastric gland cells whichwere isolated from formalin-fixed, paraffin-embedded gastric mucosal biopsy samples using laser capture microdissection were usedfor lectin microarray to obtain lectin–glycan interaction values.Results: Comparison of the lectin–glycan interaction values before and after eradication in the same patients showed significantincreases for Ricinus communis agglutinin 120, Trichosanthes japonica agglutinin II, Euonymus europaeus lectin, jacalin, Amaranthuscaudatus agglutinin, and Maclura pomifera agglutinin and significant decreases for Urtica dioica agglutinin, Lycopersicon esculentumlectin, Ulex europaeus agglutinin, Sambucus nigra agglutinin, Sambucus sieboldiana agglutinin, and Trichosanthes japonica agglutinin I.Furthermore, jacalin and MPA in the gastric antrum were significantly decreased with H. pylori infection compared with the withoutinfection group and improved to the levels seen without infection as a result of eradication. Lycopersicon esculentum lectin, Sambucusnigra agglutinin, Sambucus sieboldiana agglutinin, and Trichosanthes japonica agglutinin I in the gastric body were significantlyincreased with H. pylori infection and improved to the level seen without infection as a result of eradication.Conclusion: H. pylori infection changes the lectin binding state which is related to various cancers on the gastric mucosal cell.Furthermore, those changes are reversible by H. pylori eradication.